Evaluasi Kecernaan Protein Kasar dan Serat Kasar dari Kombinasi Fraksi Hijauan Rumput Gajah (Pennisetum purpureum) cv Taiwan dengan Legume Indigofera. sp secara In-Vitro - Sri Mulyani; Syafrizal; K Setiawati (Program Studi Peternakan, 2021)
This study aims to determine the digestibility of crude protein and crude fiber from the combination of forage fractions of Taiwan Elephant grass (Pennisetum purpureum) cv Taiwan with Legume Indigofera sp by In-Vitro. This research was conducted by experimental method using Randomized Block Design (RAK) with 5 treatments and 4 groups (different cow rumen fluid), where the combination is as follows: A is Elephant grass cv Taiwan 100% (control), B is Elephant grass cv Taiwan (75%) + Indigofera. sp (25%), C is Elephant grass cv Taiwan upper fraction (90%) + Indigofera. sp ( 10%), D is Elephant grass cv Taiwan middle fraction (80%) + Indigofera. sp (20%), E is Elephant grass cv Taiwan lower fraction (70%) + Indigofera. sp (30%). The variables measured were crude protein digestibility and crude fiberdigestibility. Analysis of variance showed that the combination treatment of Elephant grass cv taiwan with Indigofera. sp had a very significant effect (P<0.01) on the increase in crude protein digestibility and crude fiber digestibility. The DMRT follow-up test showed that the protein digestibility of treatment C = 72.86% was very significantly different (P<0.01) compared to other treatments (treatments B, D, E and control) on crude protein digestibility and the DMRT follow-up test showed that the digestibility of fiber Crude treatment C = 69.70% was significantly different (P<0.01) compared to other treatments (treatments B, D, E and control) on crude fiber digestibility. Based on the results of this study, it can be concluded that the combination of each fraction of Elephant grass cv Taiwan with Indigofera Legumes. sp can increase the digestibility of crude protein and digestibility of crude fiber.